Naturally-Occurring Canine Mammary Tumors as a Translational Model for Human Breast Cancer - Gray, Mark; Meehan, James; Martínez-Pérez, Carlos; Kay, Charlene; Turnbull, Arran K.; Morrison, Linda R.; Pang, Lisa Y.; Argyle, David (Frontiers in Oncology, 2020)
Despite extensive research over many decades, human breast cancer remains a major worldwide health concern. Although there has been an improvement in the management and survival of patients suffering from localised disease, the overall 5-year survival rate for patients diagnosed with metastatic disease remains poor, at only 25%. In vitro studies using immortalised cell lines and in vivo mouse models, typically using xenografted cell lines or patient derived material, are commonly used to study breast cancer. Although these techniques have undoubtedly increased our molecular understanding of breast cancer, these research models have significant limitations and have contributed to the high attrition rates seen in cancer drug discovery. It is estimated that only 3–6% of drugs that show promise in these pre-clinical models will reach clinical use. Animal models that more accurately reflect human breast cancer are required if progress is to be made in improving cancer drug research, treatment outcomes and prognosis. Canine mammary cancers are a naturally occurring heterogenous group of cancers that have several features in common with human breast cancer. These similarities include aetiology, histological classification and the activation of common cellular signalling pathways. Here we discuss the use of naturally-occurring canine mammary cancers as a translational animal model for human breast cancer research.